Battered woman syndrome among Iraqi women in Baghdad - Al-Nuaimy, Rwaa Sami; Alhelou, Buthaina Mansour (Al-Adab Journal, 2021)
Scientific progress and evolution of technology made many things easier for people, but at the same time the pressures of life have increased, and the burdens on the individual have increased.There are differences between individuals, each individual responds to situations and difficulties in a way differs from others, we may show positive behaviors in dealing with family difficulties and disputes.Also, one may show negative behaviors to express anger or discomfort from what he is exposed to inflicting physical and moral damage to the dearest people on him, which can be his wife, children, sister or even his mother.The current study highlights the concept of battered woman syndrome, which describes the psychological response of women who are abused and treated violently by men and is considered by some researchers as a type of behavior associated with PTSDThe current research goal is to:Identify the prevalence of battered woman syndrome.Identify battered woman syndrome in battered women.After examining the data statistically using the T-test for one sample, Pearson correlation coefficient and other statistical methods, the researcher reached the following conclusions:The prevalence of battered woman syndrome is 27.17% higher than in some other societies when compared to other studies.The members of the sample were subjected to violence, which leads to their entry into the cycle of violence. In light of these findings, the researcher presented a set of recommendations and proposals for future researches.